2015
DOI: 10.5811/westjem.2015.4.22857
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Preloaded Bougie versus Standard Bougie Technique for Endotracheal Intubation in a Cadaveric Model

Abstract: IntroductionWe compared intubating with a preloaded bougie (PB) against standard bougie technique in terms of success rates, time to successful intubation and provider preference on a cadaveric airway model.MethodsIn this prospective, crossover study, healthcare providers intubated a cadaver using the PB technique and the standard bougie technique. Participants were randomly assigned to start with either technique. Following standardized training and practice, procedural success and time for each technique was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…A literature review showed eight studies on the performance of bougies and stylets . One manikin study with 24 participants investigated FPS of the naked ETT, achieving a 46% FPS .…”
Section: Discussionmentioning
confidence: 99%
“…A literature review showed eight studies on the performance of bougies and stylets . One manikin study with 24 participants investigated FPS of the naked ETT, achieving a 46% FPS .…”
Section: Discussionmentioning
confidence: 99%
“…However, neither study involved any pediatric patients. Similarly, studies using simulated airways, 1 , 15 , 16 , 17 , 18 , 19 , 20 cadavers, 21 , 22 and patients undergoing elective surgeries 23 to compare the first‐pass success rates of bougie, stylet, and naked endotracheal tube have all used adult subjects.…”
Section: Discussionmentioning
confidence: 99%
“… 11 , 12 Research investigating the efficacy of stylets in first‐pass success in pediatric patients has been limited to 2 neonatal studies. 13 , 14 Likewise, studies using airway manikins, 1 , 15 , 16 , 17 , 18 , 19 , 20 cadavers, 21 , 22 and elective surgical patients 23 to compare the efficacy of bougie and stylet have used only adult subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Based on other studies, the success rates of bougie have been reported to range from 74% to 99% in difficult intubation. 25 In a study by Shah et al 26 to determine the success rate of endotracheal intubation in the emergency department using a plastic bougie, the device was found to have a success rate of 73.7% when used as a means of airway management in patients with difficult airways.…”
Section: Discussionmentioning
confidence: 99%